The history and value of face masks - Matuschek, Christiane; Moll, Friedrich; Fangerau, Heiner; Fischer, Johannes C.; Zänker, Kurt; Van Griensven, Martijn; Schneider, Marion; Kindgen-Milles, Detlef; Knoefel, Wolfram Trudo; Lichtenberg, Artur; Tamaskovics, Bálint; Djiepmo-Njanang, Freddy Joel; et al. (European Journal of Medical Research, 2020)
In the human population, social contacts are a key for transmission of bacteria and viruses. The use of face masks seems to be critical to prevent the transmission of SARS-CoV-2 for the period, in which therapeutic interventions are lacking. In this review, we describe the history of masks from the middle age to modern times.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Bacterial transmission; Behavior; History of medicine; Pandemic crisis; Surgical mask; Viral transmission; Wound infection